DIDACTIC CONDITIONS OF COGNITIVE ACTIVATION ACTIVITIES OF A PRESCHOOL CHILD (Pedagogy of Higher and Secondary Education, 2006)
The article deals with the problem of cognitive of a preschool pupil It gives theoretical information about didactic conditions of the activization of the process.